Exploring problem-based learning with a caring community in the development of mathematics student worksheets - Moh. Atikurrahman; Saiful Saiful; Muzayyanatun Munawwarah; Zohaib Hassan Sain (UNION : Jurnal Ilmiah Pendidikan Matematika, 2026)
Mathematics learning in senior high schools still tends to be oriented towards memorizing routine procedures and problems, thus under-developing critical thinking skills and students' socio-affective engagement. However, limited studies have integrated Caring Community values into Problem-Based Learning (PBL) in mathematics learning contexts. This study aims to describe the implementation of Problem-Based Learning (PBL) based on Caring Community in developing Student Worksheets in mathematics at Ibrahimy 2 High School Sukorejo, a boarding school. The study used a descriptive qualitative approach involving 1 mathematics teacher and 31 grade 10 students with data collection techniques in the form of observation, interviews, and documentation. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldana through the stages of collection, reduction, presentation, and drawing conclusions. The results showed that the integration of PBL with Caring Community values was able to create more contextual, collaborative, and meaningful learning. Students became more active in problem investigations, group discussions, and showed increased courage in expressing ideas and presenting work results. In addition, a supportive and emotionally safe learning environment encouraged peer scaffolding and strengthened understanding of mathematical concepts. These findings indicate that Caring Community-based PBL has the potential to be an alternative mathematics learning method that not only develops cognitive aspects, but also social and affective aspects of students, especially in the context of Islamic boarding school education. This study contributes theoretically by extending the Problem-Based Learning (PBL) framework through the integration of Caring Community values, emphasizing that socio-affective dimensions play a crucial role in supporting mathematical understanding and collaborative knowledge construction.